2005
DOI: 10.1016/j.visres.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Refractive index distribution and optical properties of the isolated human lens measured using magnetic resonance imaging (MRI)

Abstract: Using a non-invasive MRI technique for measuring the refractive index distribution through the crystalline lens, refractive index maps were obtained through 20 intact isolated human lenses (7-82years). Focal length measurements, obtained by simulated light ray propagation through each index map were found to be in agreement with direct measurements performed on a scanning laser apparatus. With increasing age, the refractive index profiles became flatter in the central region, accompanied by steepening of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
237
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(270 citation statements)
references
References 35 publications
27
237
2
4
Order By: Relevance
“…Secondly as pointed out previously [8] "The data were inherently noisy due primarily to the limited sensitivity of the clinical MRI scanner for this type of measurement and the need to minimize scan times to reduce motion artifacts and avoid fatiguing the subject." With the growing availability of clinical MRI systems operating at higher magnetic fields of 7T and above, it should become possible to obtain high resolution refractive index profiles with good signal-to-noise ratio for individual lenses, similar to those that we have obtained ex-vivo [24], particularly with the advent of dedicated receiver coils for eye imaging at these fields.…”
Section: Discussionmentioning
confidence: 74%
“…Secondly as pointed out previously [8] "The data were inherently noisy due primarily to the limited sensitivity of the clinical MRI scanner for this type of measurement and the need to minimize scan times to reduce motion artifacts and avoid fatiguing the subject." With the growing availability of clinical MRI systems operating at higher magnetic fields of 7T and above, it should become possible to obtain high resolution refractive index profiles with good signal-to-noise ratio for individual lenses, similar to those that we have obtained ex-vivo [24], particularly with the advent of dedicated receiver coils for eye imaging at these fields.…”
Section: Discussionmentioning
confidence: 74%
“…Regular and enhanced MRI detected differences between normal and cataract lenses in Lizak and colleagues study (10). Other studies show the successful use of MRI for measurement of protein distribution inside the lens and the spatial gradient of refractive index (17,18,(20)(21)(22)(23). Also, some other studies demonstrated that MRI could be used as an effective method to diffusivity mapping of the lens (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…detector elements, it can be shown that ML estimation according to Eq. (3) reduces to nonlinear least-squares fitting between the data and the output of the optical design program: (4) Immediate advantages are that ML estimation is efficient (i.e., unbiased and yields the best possible variance) if an efficient estimator exists, and that it is asymptotically unbiased as more photons are acquired. However, one challenge is that an accurate probability model must be used that includes all sources of randomness (e.g., photon noise and electronic noise) [33] as well as fluctuations of ocular aberrations associated with live imaging of the eye, including the tear film effect.…”
Section: Maximum-likelihood Estimationmentioning
confidence: 99%
“…Accurate determination of optical parameters in normal and abnormal eyes could also be valuable in developing data bases for clinical diagnosis of pathologies, while measurements of ocular surface misalignments would be useful after implantation of intraocular lenses in cataract surgery [1][2][3]. Moreover, knowledge of the refractive index distribution in the lens may be beneficial in optical coherence tomography, which is based on interferometric reflectometry and index changes [4,5]. It could additionally lead to a substantial improvement in retinal imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation